Comparing Super-Resolution Microscopy Techniques to Analyze Chromosomes - Kubalová, Ivona; Němečková, Alžběta; Weisshart, Klaus; Hřibová, Eva; Schubert, Veit (International journal of molecular sciences, 2021)
The importance of fluorescence light microscopy for understanding cellular and sub-cellular structures and functions is undeniable. However, the resolution is limited by light diffraction (~200-250 nm laterally, ~500-700 nm axially). Meanwhile, super-resolution microscopy, such as structured illumination microscopy (SIM), is being applied more and more to overcome this restriction. Instead, super-resolution by stimulated emission depletion (STED) microscopy achieving a resolution of ~50 nm laterally and ~130 nm axially has not yet frequently been applied in plant cell research due to the required specific sample preparation and stable dye staining. Single-molecule localization microscopy (SMLM) including photoactivated localization microscopy (PALM) has not yet been widely used, although this nanoscopic technique allows even the detection of single molecules. In this study, we compared protein imaging within metaphase chromosomes of barley via conventional wide-field and confocal microscopy, and the sub-diffraction methods SIM, STED, and SMLM. The chromosomes were labeled by DAPI (4',6-diamidino-2-phenylindol), a DNA-specific dye, and with antibodies against topoisomerase IIα (Topo II), a protein important for correct chromatin condensation. Compared to the diffraction-limited methods, the combination of the three different super-resolution imaging techniques delivered tremendous additional insights into the plant chromosome architecture through the achieved increased resolution.
Keywords: photoactivated localization microscopy; Single Molecule Imaging; DNA-topoisomerasy typu II; Fluorescent Dyes; structured illumination microscopy; Metaphase; konfokální mikroskopie; fluorescenční mikroskopie; indoly; Hordeum; Hordeum vulgare; topoisomerase II; DNA Topoisomerases, Type II; nanoscopy; reprodukovatelnost výsledků; chromozomy rostlin; stimulated emission depletion microscopy; Chromosomes, Plant; Reproducibility of Results; chromatin; Microscopy, Confocal; Microscopy, Fluorescence; metaphase chromosome; Indoles; ječmen (rod); wide-field microscopy; deconvolution microscopy; fluorescenční barviva; zobrazení jednotlivé molekuly; metafáze